Effects of Different Intensity Modulator On The Generation of MM-Waves in RoF System. Issue 1 (1st August 2022) - Gupta, Raghav; Singh, Ajmer
Abstract: The increasing demand of wireless network has strongly take interests of new transmission systems. A phase shift of 80 GHz – 120 GHz is achieved for the millimeter wave by using SBS technique that is beneficial for the 5G networks. RoF technique requires the optical modulators in the transmitter side. Performance of different modulators such as Amplitude Modulator, Phase Modulator, Electro Absorption Modulator, and Mach Zehnder Modulator is analyzed in this demonstrated work. Performance comparison of all modulators shows that the SNR (93.32) and output power (71.56) of the system is maximum in MZM. Results shows that the system has the high power, good SNR and enhanced frequency shifts.